The Frequency of Ischemic Stroke Associated with Atrial Fibrillation at a Tertiary Care Hospital (Bangladesh Journal of Medical Science, 2023)
Acute ischemic stroke is most commonly associated with atrial fibrillation. However, its prognostic impact on patients with acute cerebrovascular accidents is not fully clarified. Stroke associated with AF is associated with the worst outcome as compared to without atrial fibrillation. Atrial fibrillation is present in 20–30% of patients affected by stroke. Also, in Pakistan the prevalence of atrial fibrillation with ischemic stroke patients is still unknown.Objective: To determine the association of atrial fibrillation with acute ischemic stroke.Material & methods: This cross-sectional analytical study was conducted at Neurology ward of Aga Khan University Hospital, Karachi, over eight months from 19th May 2020 to 18th December 2020. A total of two hundred sixteen patients who were admitted with the diagnosis of ischemic stroke were included in the study.Results: The 216 patients with first-ever acute ischemic stroke for more than 24 hours, age range between 30 and 80 years, both male and female were included in the study. The mean systolic blood pressure SBP and diastolic blood pressure DBP was 132.64±17.68 & 84.45±15.01 & mean duration of diabetes mellitus in new onset ischemic stroke patients was 11.1±6.61years male outnumbered females, with 78(36%) women and 138(64%) men.Conclusion: In summary, it was found that incidence of atrial fibrillation with ischemic stroke is most common among Pakistani population.Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 91-96